2008
DOI: 10.1017/s0266462308080562
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of single use medical devices in Canada: Clinical and economic outcomes, legal and ethical issues, and current hospital practice

Abstract: There is insufficient evidence to establish the safety, efficacy and cost-effectiveness of reusing SUDs. Legal and ethical issues require attention to minimize liability and maintain patient safety and trust. Some hospitals that reprocess SUDs do not have adequate documentation. These findings do not support the reuse of SUDs in Canadian hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 16 publications
0
34
1
2
Order By: Relevance
“…[1][2][3][4][5][6][7] However, serious concerns about safety and even efficacy have been raised about this practice. [8][9][10][11][12][13] A few studies have reported on this issue in recent years and found no solid evidence against this procedure. [1][2][3][4][5][6][7] In our institution, a tertiary referral center, cadaveric donation with subsequent resterilization and implantation of these reused pacemaker has been a common practice for patients for whom a new device cannot be obtained by other means or strategies.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, serious concerns about safety and even efficacy have been raised about this practice. [8][9][10][11][12][13] A few studies have reported on this issue in recent years and found no solid evidence against this procedure. [1][2][3][4][5][6][7] In our institution, a tertiary referral center, cadaveric donation with subsequent resterilization and implantation of these reused pacemaker has been a common practice for patients for whom a new device cannot be obtained by other means or strategies.…”
mentioning
confidence: 99%
“…Evidences for the possibility to sterilize the single use devices even with the contamination-challenge are present [25]. For economic issues we safely re-used vessel sealing bipolar devices several times which could be cost-effective [22] [26] [27]. The cost has been reduced by about 70% that means 500 US Dollars at the time of the study which is a good financial benefit regarding Egypt economy.…”
Section: Discussionmentioning
confidence: 99%
“…The judicious choice of disposable and reusable instruments could provide the best possible tools for the surgeons in developing countries to perform laparoscopic procedures provided that patient safety and oncologic feasibility could be maintained [27] [28].…”
Section: Discussionmentioning
confidence: 99%
“…The list includes surgical saw blades, surgical drills, laparoscopy scissors, orthodontic braces, electrophysiology catheters, electrosurgical electrodes, respiratory therapy and anesthesia breathing circuits, endotracheal tubes, balloon angioplasty (PTCA) catheters and biopsy forceps. But, there is still uncertainty regarding the safety and effectiveness of the reuse of single use devices (Hailey et al, 2008).…”
Section: Re-use Of Single Use Devicesmentioning
confidence: 99%
“…Some of them are the surveys of medical device accidents and user errors (Carol, 2003;Hijazi, 2011;Brennan, 1991;Sawyer, 1997;Sezdi, 2009a). Some of them are focused on only electrical safety (Barbosa et al, 2010;Osman et al, 1996;Chakrabartty et al, 2010;Bakes, 2007;Sezdi, 2009b), whereas the others examined both the sterilization and reusage of single use devices related to the patient safety (Yoleri, 2011;Rice et al, 2009;Quirk, 2002;Northrup, 2000;Day, 2004;Koh, 2005;Buchdid Amarante, 2008;Hailey et al, 2008). There are also studies that explain the classification of clean rooms by measuring particles (Sezdi, 2009c).…”
mentioning
confidence: 99%